Why Detailing Spatial Equity Matters in Water and Sanitation Evaluations. Issue 1 (2nd January 2021) - Carolini, Gabriella Y.; Raman, Prassanna
Abstract: Efficiency metrics in water and sanitation performance benchmarking are widely referenced, even where the most serious challenge facing cities is actually extending the service reach of public water and sanitation systems. Critical scholarship on water governance gives water and sanitation planners reason to question whether such performance benchmarks are universally appropriate references. This is especially the case where there is not yet universal water and sanitation coverage. In such environments, the extensive use of efficiency-based benchmarks couple with the growth of financialization to create vulnerabilities for equity-based objectives. Citizen report cards represent an important, spatially informed alternative for assessing utilities' performances.